Liver metastasis of a neuroendocrine neoplasm of unknown primary origin in a female patient with a history of breast cancer - Struk-Panfill, Małgorzata; Błaut, Krzysztof; Pęksa, Rafał; Kmieć, Piotr; Sworczak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2018)
We report on and discuss a case of a female patient diagnosed with breast cancer in 1996, which was histopathologically assessed as an invasive ductal carcinoma. The patient was admitted to our Department in 2017 with a liver metastasis of a neuroendocrine tumour. On admission she had no symptoms of an endocrinopathy and was in a good general condition. Due to unknown primary site of the metastasis and given the patient’s history of breast cancer, it was suspected that the breast cancer was in fact a neuroendocrine tumour. This hypothesis was confirmed by comparing histopathological specimens of the breast and liver tumours using advanced pathological methods.